Body-subjects and disordered minds - Matthews, Eric, 1936- (International perspectives in philosophy and psychiatry., 2007)
How should we deal with mental disorder - as an 'illness' like diabetes or bronchitis, as a 'problem in living', or what? This book seeks to answer such questions by going to their roots, in philosophical questions about the nature of the human mind, the ways in which it can be understood, and about the nature and aims of scientific medicine.